Development of a sustainable binder made of recycled high-performance concrete (HPC). (December 2022) - Daneshvar, Dana; Liberto, Teresa; Dalconi, Maria Chiara; Stöllinger, Waltraud; Kirnbauer, Johannes; Robisson, Agathe
Abstract: The high consumption of ordinary Portland cement (OPC) in high-performance concrete (HPC), combined with the growing accumulation of construction and demolition wastes (CDW), raises severe environmental and economic concerns. This study addresses both issues by proposing a novel sustainable binder made of milled recycled HPC (mRHPC). A series of HPC mix designs (R-HPC) was developed replacing OPC by mRHPC (0–100%), and characterized in fresh and hardened states. The residual reactivity of mRHPC was detected using X-ray diffraction, calorimetry, and rheological oscillatory measurements (SAOS). Replacement up to 30% resulted in comparable 28-day compressive and flexural strengths to that of the OPC reference specimen while slightly improving fresh properties. Furthermore, the performance of steel fiber reinforced R-HPC overlays was investigated in repair application, and 30% replacement ratio enhanced the tensile bond strength by a factor of 2.4. The measured improved flow properties and reduced drying shrinkage can explain this remarkable result.